2021
DOI: 10.1002/advs.202100332
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Confinement Effects of Semiconducting Polymers in Polymer Blend Electronic Systems

Abstract: The advent of special types of polymeric semiconductors, known as "polymer blends," presents new opportunities for the development of next-generation electronics based on these semiconductors' versatile functionalities in device applications. Although these polymer blends contain semiconducting polymers (SPs) mixed with a considerably high content of insulating polymers, few of these blends unexpectedly yield much higher charge carrier mobilities than those of pure SPs. However, the origin of such an enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
(122 reference statements)
1
14
0
Order By: Relevance
“…Two-component polymer semiconductor/insulator composite systems have been well studied previously. However, most of them improved mechanical stretchability but reduced charge carrier mobilities. The elastomeric systems reported in the literature include PDMS, polystyrene- block -poly­(ethylene- ran -butylene)- block -polystyrene (SEBS), , butyl rubber (BR), and polyurethane . However, we discovered through proper selection of the elastomer that a conjugated polymer/elastomer phase-separation-induced elasticity (CONPHINE) can result in both increased charge carrier mobilities and improved mechanical properties compared to the corresponding neat polymer semiconductors (Figure B) .…”
Section: Multicomponent Systemsmentioning
confidence: 99%
“…Two-component polymer semiconductor/insulator composite systems have been well studied previously. However, most of them improved mechanical stretchability but reduced charge carrier mobilities. The elastomeric systems reported in the literature include PDMS, polystyrene- block -poly­(ethylene- ran -butylene)- block -polystyrene (SEBS), , butyl rubber (BR), and polyurethane . However, we discovered through proper selection of the elastomer that a conjugated polymer/elastomer phase-separation-induced elasticity (CONPHINE) can result in both increased charge carrier mobilities and improved mechanical properties compared to the corresponding neat polymer semiconductors (Figure B) .…”
Section: Multicomponent Systemsmentioning
confidence: 99%
“…The d L−L for the blend films was found to be slightly higher, compared to the neat films, which is consistent with the results reported previously. 27 Compared to the neat films, the d π−π for the blend films was also slightly higher, but it can be maintained at about 3.6 Å. The calculation results of full width at half maximum showed that the coherence length decreased significantly after blending, indicating a reduced crystallinity of the blend films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In general, three types of molecular interactions govern the phase separation between SPs and IPs, including interactions between solute–solvent, solute–substrate, and solute–solute, which lead to a specific structure and properties of the blend film . So far, both vertical and lateral phase separation between SPs and IPs are primarily regulated by controlling different factors affecting these three types of interactions, depending on the blend composition (molecular weight, molecular structure, and blend ratio) and processing conditions (technology, solvent, temperature, and aging time). Despite some success in blend composition, there is still limited literature, devoted to the systematic investigation of the effects of molecular weight on phase separation of the blend films. Only a few studies have recently been reported, for example, the molecular weight of semiconductor PTDPP and insulator SEBS in the blend film system.…”
Section: Introductionmentioning
confidence: 99%
“…10c). 140 Based on the correlation between the morphological and charge transport properties on various types of SP:IP blend films, it was found that the 29-DPP-type SP exhibited an improvement in field-effect hole mobilities by 3–4 times (maximum μ FET h approaching 10 cm 2 V −1 s −1 for 60DPP:40PS blended type). The combination of temperature-dependent charge carrier mobility analysis and grazing incident-wide angle X-ray spectroscopy (GIWAXS) indicated that the nanostructure of confined SPs exhibited a straight edge-on stacking structure in the blends.…”
Section: Stretchable Semiconducting Polymersmentioning
confidence: 99%